If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -2a = 9 Reorder the terms: -2a + 3b = 9 Solving -2a + 3b = 9 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. -2a + 3b + -3b = 9 + -3b Combine like terms: 3b + -3b = 0 -2a + 0 = 9 + -3b -2a = 9 + -3b Divide each side by '-2'. a = -4.5 + 1.5b Simplifying a = -4.5 + 1.5b
| 20-4c=-68 | | X(x+2)-2(x+2)= | | 6(3x-1)-2x=2(2x-5)-8 | | 5x+3=7x | | q=7(p-2)+3 | | 5w+30=2w+36 | | y=4.7x^2+4.5x+40 | | 6f=120 | | 2y-7=-1y-2y | | 6n-12=3(2n-4) | | 12t^2-4t=-3 | | 2[s+3(s-1)]=18 | | 3a-2b=9 | | 12d=48 | | 8x-6=3x-26 | | -111+2s=9 | | 6n-12=(2n-4) | | 5x-12=7x+8 | | 2a-24-31=5a | | x-1.75=24 | | 15x+9=12x | | 6(-9x-7)=5(12x-12) | | 37-18-(8x)=67 | | 18=2k-4 | | 4x-10=-4x+21 | | 18=2k-4 | | 2(y+p)=3p+s | | 37-18-8x-6=x | | x^2+11x+7=0 | | 5x+180-3x=220 | | 17+2t=37 | | 3X+-2=4 |